Sex differences in prehospital delays in patients with st-segment-elevation myocardial infarction undergoing percutaneous coronary intervention - Stehli, J.; Dinh, D.; Dagan, M.; Duffy, S.J.; Brennan, A.; Smith, K.; Andrew, E.; Nehme, Z.; Reid, Christopher; Lefkovits, J.; Stub, D.; Zaman, S. (WILEY, 2021)
BACKGROUND: Women with ST-segment-elevation myocardial infarction experience delays in reperfusion compared with men with little data on each time component from symptom onset to reperfusion. This study analyzed sex discrepancies in patient delays, prehospital system delays, and hospital delays. METHODS AND RESULTS: Consecutive patients with ST-segment-elevation myocardial infarction treated with percutaneous coronary intervention across 30 hospitals in the Victorian Cardiac Outcomes Registry (2013-2018) were analyzed. Data from the Ambulance Victoria Data warehouse were used to perform linkage to the Victorian Cardiac Outcomes Registry for all patients transported via emergency medical services (EMS). The primary end point was EMS call-to-door time (prehospital system delay). Secondary end points included symptom-to-EMS call time (patient delay), door-to-device time (hospital delay), 30-day mortality, major adverse cardiovascular events, and major bleeding. End points were analyzed according to sex and adjusted for age, comorbidities, cardiogenic shock, cardiac arrest, and symptom onset time. A total of 6330 (21% women) patients with ST-segment-elevation myocardial infarction were transported by EMS. Compared with men, women had longer adjusted geometric mean symptom-to-EMS call times (47.0 versus 44.0 minutes; P<0.001), EMS call-to-door times (58.1 versus 55.7 minutes; P<0.001), and door-to-device times (58.5 versus 54.9 minutes; P=0.006). Compared with men, women had higher 30-day mortality (odds ratio [OR], 1.38; 95% CI, 1.06-1.79; P=0.02) and major bleeding (OR, 1.54; 95% CI, 1.08-2.20; P=0.02). CONCLUSIONS: Female patients with ST-segment-elevation myocardial infarction experienced excess delays in patient delays, prehospital system delays, and hospital delays, even after adjustment for confounders. Prehospital system and hospital delays resulted in an adjusted excess delay of 10 minutes compared with men.